Thematic analysis in social media influencers: who are they following and why? - Alves de Castro, Charles (Frontiers in Communication, 2023)
The focus of this study is to holistically analyse the influence of social media influencers' content on young people's lives in Ireland. To address this main objective, this study aimed to answer the following research question: Who are the five preferred influencers that this young sample follows and what are their motives for following them? To answer these questions, this study analysed two free-answer questions that were part of a longer questionnaire via thematic analysis using NVivo. This study's sample population comprised 81 participants between 16 and 26 years old, part of the Generation Z cohort and living in Ireland. The results of the analysis indicated five main motives that make this young sample follow their preferred social media influencers. Furthermore, the findings in this study confirm that the sample is susceptible to being influenced by SMIs in different contexts. In this regard, three drivers play a crucial role consist of parasocial relationship, trust, and relatability. Finally, the insights discovered in this research can provide essential information to marketers to support the development of more effective marketing communication strategies.